Expression of the NUP153 and YWHAB genes from their canonical promoters and alternative promoters of the LINE-1 retrotransposon in the placenta of the first trimester of pregnancy - V. V. Demeneva; E. N. Tolmacheva; T. V. Nikitina; E. A. Sazhenova; S. Yu. Yuriev; A. Sh. Makhmutkhodzhaev; A. S. Zuev; S. A. Filatova; A. E. Dmitriev; Ya. A. Darkova; L. P. Nazarenko; I. N. Lebedev; et al. (Вавиловский журнал генетики и селекции)
The placenta has a unique hypomethylated genome. Due to this feature of the placenta, there is a potential possibility of using regulatory elements derived from retroviruses and retrotransposons, which are suppressed by DNA methylation in the adult body. In addition, there is an abnormal increase in the level of methylation of the LINE-1 retrotransposon in the chorionic trophoblast in spontaneous abortions with both normal karyotype and aneuploidy on different chromosomes, which may be associated with impaired gene transcription using LINE-1 regulatory elements. To date, 988 genes that can be expressed from alternative LINE-1 promoters have been identified. Using the STRING tool, genes (NUP153 and YWHAB) were selected, the products of which have significant functional relationships with proteins highly expressed in the placenta and involved in trophoblast differentiation. This study aimed to analyze the expression of the NUP153 and YWHAB genes, highly active in the placenta, from canonical and alternative LINE-1 promoters in the germinal part of the placenta of spontaneous and induced abortions. Gene expression analysis was performed using real-time PCR in chorionic villi and extraembryonic mesoderm of induced abortions (n = 10), adult lymphocytes (n = 10), spontaneous abortions with normal karyotype (n = 10), and with the most frequent aneuploidies in the first trimester of pregnancy (trisomy 16 (n = 8) and monosomy X (n = 6)). The LINE-1 methylation index was assessed in the chorionic villi of spontaneous abortions using targeted bisulfite massive parallel sequencing. The level of expression of both genes from canonical promoters was higher in blood lymphocytes than in placental tissues (p < 0.05). However, the expression level of the NUP153 gene from the alternative LINE-1 promoter was 17 times higher in chorionic villi and 23 times higher in extraembryonic mesoderm than in lymphocytes (p < 0.05). The expression level of NUP153 and YWHAB from canonical promoters was higher in the group of spontaneous abortions with monosomy X compared to all other groups (p < 0.05). The LINE-1 methylation index negatively correlated with the level of gene expression from both canonical (NUP153 – R = –0.59, YWHAB – R = –0.52, p < 0.05) and alternative LINE-1 promoters (NUP153 – R = –0.46, YWHAB – R = –0.66, p < 0.05). Thus, the observed increase in the LINE-1 methylation index in the placenta of spontaneous abortions is associated with the level of expression of the NUP153 and YWHAB genes not only from alternative but also from canonical promoters, which can subsequently lead to negative consequences for normal embryogenesis.